Friends and neighbors: group life in America's first plural society - Zuckerman, Michael (Temple Univ. Pr, 1982)
Introduction: Puritans, Cavaliers, and the motley middle / by Michael Zuckerman -- The birth of the "modern family" in early America / by Barry Levy -- The Scottish proprietors and the planning of east New Jersey / by Ned Landsman -- The roots of Episcopalian authority structures / by Deborah Mathias Gough -- Power challenged / by Valerie G. Gladfelter -- Quaker tribalism / by Susan S. Forbes -- The Quaker connection / by Nancy Tomes -- Diversity and its significance in an eighteenth-century Pennsylvania town / by Laura L. Becker -- This Tory labyrinth / by Wayne Bodle